Pengembangan Pemasaran Produk Bibit Tanaman di Dusun Baringin Gadut Dengan Digitalisasi - Fajri Rinaldi Chan; Muhammad Imam Dwi Maulana (BALQIS : Journal of Business Innovation and Digital Marketing, 2025)
This study explores the development of seedling product marketing in Baringin Gadut Hamlet through the implementation of digitalization strategies aimed at overcoming the limitations of conventional marketing practices. Despite the area’s significant potential in the plant nursery sector, its market reach and competitiveness have remained low due to reliance on traditional distribution methods. This research seeks to design and implement a digital marketing model that not only enhances economic outcomes but also empowers the local community. A qualitative descriptive approach was employed, involving interviews, field observations, surveys, and document analysis with plant seed entrepreneurs, local communities, and related stakeholders. The research process included community needs assessment, digital marketing training, the implementation of an online store platform, and evaluation of its effectiveness. Findings reveal that the OpenCart-based BITO online store, complemented by intensive training in social media and e-commerce use, successfully expanded market access and improved sales efficiency. Within the first month, BITO recorded multiple out-of-region transactions, indicating increased competitiveness of local products. Challenges such as limited digital literacy and internet infrastructure were addressed through stepwise training, mentoring, and technical adaptations of the platform, including features designed for low connectivity. Beyond improving income, the initiative contributed to building community confidence and skills in digital technology, fostering long-term empowerment. Overall, this study demonstrates that integrating digitalization with community capacity-building provides a sustainable model for rural agribusiness development and offers a replicable strategy for similar regions